Analysis of Vegetation Index Values and Sugar Content in Sugarcane Based on Planting Age using Sentinel-2 Satellite Data - Inas Alfiyatul Umniyah; Bowo Eko Cahyono; Agus Suprianto; Farid Lukman Hakim (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
This study the relationship between the age of sugarcane plants (Saccharum officinarum L.), vegetation indices, and sugar content using Sentinel-2 satellite imagery in Jember Regency. Vegetation indices such as NDVI, GNDVI, NDRE, and NDII were used to monitor the physiological condition of the plants, while sugar content was measured using a refractometer on the upper, middle, and lower sections of the sugarcane stalks. The results indicate that the highest sugar content was found in the lower stalk section, as this area serves as the primary storage site for sucrose. There is relationship that increasing plant age correlates with changes in vegetation index patterns, peaking during the maximum vegetative phase. These findings offer significant insights into technology-based sugarcane land management, supporting the optimization of harvest timing, irrigation, and fertilization.